PERAN GREENPEACE DALAM PENANGANAN POLUSI UDARA DAN AIR DI INDIA - Subyadi, Pani; Retnaningsih, Umi Oktyari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research explores the role of Greenpeace as a non-governmental organization in addressing the issue of air and water pollution in India, which has become a critical environmental challenge. which aims to analyze the role of Greenpeace in addressing air and water pollution in India. Pollution is one of the most pressing environmental issues in India, negatively impacting public health and ecosystems. Greenpeace, as a non-governmental organization focused on environmental issues, has sought to raise awareness and encourage action on this issue through various campaigns and initiatives. The methodology used in this research is a qualitative approach with secondary data collection from related literature, reports and documents. This research also identifies the strategies implemented by Greenpeace in addressing pollution, as well as the challenges faced in its implementation. The results show that Greenpeace has played an active role in policy advocacy, public education, and community mobilization to address air and water pollution. Despite some progress, challenges such as industry resistance and lack of government support remain significant obstacles. This research is expected to contribute to the understanding of the role of environmental organizations in addressing pollution issues in developing countries, as well as provide recommendations for more effective strategies in future environmental protection efforts. Keywords: water air pollution in India, Greenpeace, role, clean air nation, Namami ganges